ANALISIS MINERAL PEMBENTUK FACIES GUA SALUKANG KALLANG KAWASAN KARST TAMAN NASIONAL BANTIMURUNG BULUSARAUNG MAROS - Sari, Rati Puspita; Arsyad, Muhammad; Tiwow, Vistarani Arini (Jurnal Sains dan Pendidikan Fisika, 2019)
Research has been done for the purpose of describing the characteristics of the Kallang Salukang Cave and analyzing the mineral content of cave caridoid that include a sample of cave ornaments such as stalactites, stalactites, lime, sand and soil done in Laboratory of Microstructure of FMIPA UNM using X-Ray Diffraction (XRD) method. From the results of the research in which the characteristics of the Salukang Kallang Cave can be found flora, fauna, and is a cave that is still active characterized by the presence of water seepage in cave ornaments and the existence of a low-temperature underground river that is 26o C and high humidity up to 96.1% with light varying equal to 0 characterized by the existence of moss plants. And the temperature for the outside of the cave is 28o C, with a humidity of 94.8% and the maximum light varying 127 lux. And the results of the analysis of the mineral content of cave ornaments with the method X-Ray Diffraction (XRD) namely a sample stalactites, stalagmite, lime in caves and outer limestone caves containing calcite (CaCO3) of 100%, the dominant sand containing SiO2 of 93% and land Contains SiO2 of 47%.